The failure of conflict early warning systems in preventing the 2017 insurgency in Mozambique’s Cabo Delgado Province - Schoeman, Maxi (University of Pretoria, 2024)
Mini Dissertation (MA (Security Studies))--University of Pretoria, 2023.